Hysterosalpingography Findings and Jimah Ratio of the Uterine Cavity in Women with Infertility in Central Region, Ghana - Bashiru Babatunde Jimah; Philip Gorleku; Anthony Baffour Appiah (Radiology Research and Practice)
Background. Infertility affects from 1.3% to 25.7% of couples worldwide and, especially, from 14.5% to 16.4% in Africa. Hysterosalpingography (HSG) is a diagnostic modality that is considered both common and efficient. It is used to investigate abnormalities of the uterine cavity and fallopian tubes. This study assessed the spectrum of findings on HSG among women with infertility in the Central Region (Ghana). Methods. We conducted a prospective cross-sectional study to examine 203 infertile women undergoing HSG work-up at the Cape Coast Teaching Hospital. The exclusion criteria were acute infection of the vagina or cervix and active vaginal bleeding or pregnancy. Data were entered with Microsoft Excel and analyzed using SPSS version 21. Results. A total of 203 women were enrolled, and eighty-five (41.87%) of the women had at least one or more abnormalities. The mean age was 32.9 years with majority of the women within 30–39 years (61.08%). More than half (50.74%) of the women presented with secondary infertility, while age of women (p=0.004) and duration of infertility (0.034) were found to be in association with the type of infertility. Uterine findings were predominantly capacious uterine cavity (45.1%) and uterine fibroids (33.3%), while fallopian tube findings included bilateral blockage (24.2%), right unilateral proximal blockage (17.7%), loculated spillage (16.1%), and left unilateral proximal blockage (16.1%). The range of normal uterine cavity size, measured as ratio (Jimah ratio) of intercornual diameter to interiliac diameter was 0.2–0.45, with a mean of 0.36. Conclusion. Secondary infertility was the commonest indication for HSG in the study, and a significant proportion of infertile women had abnormalities. Abnormalities were higher in the fallopian tubes than the uterus, while capacious uterine cavity, uterine fibroid, and bilaterally blocked tubes were the top three abnormalities found.